2002
DOI: 10.1128/jvi.76.1.178-184.2002
|View full text |Cite
|
Sign up to set email alerts
|

Furin Is Involved in Baculovirus Envelope Fusion Protein Activation

Abstract: . A specific inhibitor was used to show that furin is involved in cleavage of the precursor envelope fusion (F 0 ) protein. BV produced in the presence of the inhibitor possesses the uncleaved F 0 protein, while an F protein with a mutation in the furin cleavage site was translocated to the plasma membrane but lost its fusogenic activity. These results indicate that cleavage of F 0 is required to activate the SeMNPV F protein and is necessary for BV infectivity. Specific antibodies against F 1 and against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 52 publications
2
55
0
2
Order By: Relevance
“…6A). This point mutation, an arginine-to-lysine substitution in a critical residue in the consensus furin cleavage site, was previously shown to prevent F protein cleavage (33). Using two protocols for testing gp64 complementation, we found that the F protein containing the Se8 K149 mutation did not complement the gp64-null bacmid (see Table 1).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…6A). This point mutation, an arginine-to-lysine substitution in a critical residue in the consensus furin cleavage site, was previously shown to prevent F protein cleavage (33). Using two protocols for testing gp64 complementation, we found that the F protein containing the Se8 K149 mutation did not complement the gp64-null bacmid (see Table 1).…”
Section: Resultsmentioning
confidence: 90%
“…The consensus furin cleavage site [R-X-(R/K)-R] is conserved at a similar position in F proteins from group II NPVs and GVs. Recent biochemical and mutagenic studies of the SeMNPV F protein strongly suggested that the SeMNPV F protein is cleaved by a PPC or furin protease (33). To determine whether cleavage at the furin cleavage site is essential for rescue of the gp64-null virus by the SeMNPV F protein, we generated a gp64-null bacmid expressing a SeMNPV F protein with a point mutation in the furin cleavage site (Se8 K149 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein is involved in attachment of BVs to the cell, is required for low-pH-triggered membrane fusion during virus entry and is necessary later in the process of infection for efficient budding of progeny nucleocapsids (NCs) into the haemolymph or cell-culture supernatant (Blissard & Wenz, 1992;Hefferon et al, 1999;Oomens & Blissard, 1999). envelope fusion proteins, the baculovirus F protein must be cleaved post-translationally by a proprotein convertase (furin) to become fusiogenic (Lung et al, 2002;Westenberg et al, 2002). Homologues of the F gene have been identified in other group II NPVs, in beta-and deltabaculoviruses and in members of the insect retrovirus family Errantiviridae, but also exist in group I NPVs (Herniou et al, 2003;Malik et al, 2000;Rohrmann & Karplus, 2001;Terzian et al, 2001).…”
Section: Introductionmentioning
confidence: 99%